2015
DOI: 10.3892/or.2015.3930
|View full text |Cite
|
Sign up to set email alerts
|

Pooled analysis of Swedish case-control studies during 1997–2003 and 2007–2009 on meningioma risk associated with the use of mobile and cordless phones

Abstract: Abstract.A pooled analysis of two case-control studies on meningioma with patients diagnosed during 1997-2003 and 2007-2009 was conducted. Both genders were included, aged 20-80 and 18-75 years, respectively, at the time of diagnosis. Population-based controls, matched according to age and gender, were enrolled. Exposure was assessed by questionnaire. In the entire study, cases with all brain tumor types were included. The whole reference group was used in the unconditional logistic regression analysis on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…An even more increasing rate of brain tumours in the future may be predicted based on these data. In contrast the data do not show a statistically significant increase of the rate of meningioma, a tumour type that has no consistent association with use of wireless phones [ 8 , 48 ]. Only ionizing radiation is since before an established risk factor for brain tumours.…”
Section: Discussionmentioning
confidence: 99%
“…An even more increasing rate of brain tumours in the future may be predicted based on these data. In contrast the data do not show a statistically significant increase of the rate of meningioma, a tumour type that has no consistent association with use of wireless phones [ 8 , 48 ]. Only ionizing radiation is since before an established risk factor for brain tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In meningiomas 8 case control studies were identified (Table 2 ) [ 9 11 , 13 , 14 , 16 , 18 , 20 ]. A pooled analysis of two Swedish case-control studies on 1625 meningioma patients and 3530 control patients showed a relative increased risk (OR = 1.2, CI = 0.9–1.6) among heavy users of mobile and cordless phones [ 18 ]. The INTERPHONE study that has been analyzed previously, reported no increased risk of meningioma in individuals that used a mobile phone [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar methods were used in all of our studies. Detailed information on materials and methods has been published previously [ 8 10 ]. In short, 6 administrative regions with oncology centres covering Sweden registered new cancer cases.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years the evidence has strengthened for an increased risk for these tumor types whereas the results for meningioma are less clear [ 6 12 ]. The same research groups as for glioma included also meningioma in their case-control studies with a separate publication on meningioma by Carlberg and Hardell [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation